2011
DOI: 10.1108/00346651111181985
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical and sensory evaluation of “poundmix” from yam, cocoyam, breadfruit and plantain blends

Abstract: PurposeThe purpose of this paper is to develop poundmix for reconstitution as pounded yam, from yam, cocoyam, breadfruit and plantain and to evaluate their physico‐chemical and sensory properties.Design/methodology/approachInstant flour of the components was prepared separately and 30‐50 per cent composite blends of poundmix were formulated. The physico‐chemical, and sensory properties of the poundmix were determined and the results were subjected to appropriate statistical analysis.FindingsThe swelling capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The dried yam cubes were milled with attrition mill and packaged. Cocoyam flour, breadfruit flour and plantain flour were similarly prepared with appropriate modifications according to the method of Oladeji and Akanbi (2011).…”
Section: Processing Of the Instant Floursmentioning
confidence: 99%
“…The dried yam cubes were milled with attrition mill and packaged. Cocoyam flour, breadfruit flour and plantain flour were similarly prepared with appropriate modifications according to the method of Oladeji and Akanbi (2011).…”
Section: Processing Of the Instant Floursmentioning
confidence: 99%
“…Different drying methods may show differential alterations to thermochemical processes in foods and may result in specific changes to nutritional, rheological and sensory qualities of the dried products derived from such crops. Previous studies have focused on production and quality assessments of instant poundo flours produced from yam and cassava blends (Babajide et al ., 2010), yam and moringa seeds (Kanu & Kingsley, 2020), soy‐yam blends (Malomo et al ., 2012) and poundmix from yam, cassava, breadfruit and plantain blends (Oladeji & Akanbi, 2011). To the best of authors’ knowledge, no study has reported the sole use of cocoyam in poundo flour production.…”
Section: Introductionmentioning
confidence: 99%
“…Composite meals have been developed from African breadfruit and tubers such as sweet potatoes, yam and cocoyam (Akubor, 1997;Oladeji and Akanbi, 2011) and cereals like sorghum (Onweluzo and Nnamuchi, 2009) but enrichment of breadfruit with cowpea which has the potential of alleviating protein-energy malnutrition among children in Nigeria has not received considerable attention. Due to the high dependence on breadfruit as a staple food in tropical Africa, coupled with the low nutritive value of the commodity, it is imperative to investigate simple processing method that can improve the nutrition qualities of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Cowpea has been reported to contain about 20.07 to 24.60% protein, 46.84 to 53.63 starch (carbohydrate), 1.77 to 1.96% fat and 4.27 to 4.96% fibre (Preet and Punia, 2000), as well as 3.50% ash (Darfour et al, 2012). The black-eyed cowpea (Vigna unguiculata) used for this research is an important food legume in Nigeria.Composite meals have been developed from African breadfruit and tubers such as sweet potatoes, yam and cocoyam (Akubor, 1997;Oladeji and Akanbi, 2011) and cereals like sorghum (Onweluzo and Nnamuchi, 2009) but enrichment of breadfruit with cowpea which has the potential of alleviating protein-energy malnutrition among children in Nigeria has not received considerable attention. Due to the high dependence on breadfruit as a staple food in tropical Africa, coupled with the low nutritive value of the commodity, it is imperative to investigate simple processing method that can improve the nutrition qualities of the crop.…”
mentioning
confidence: 99%